2021
DOI: 10.3389/fendo.2021.731966
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Actions of Glycoprotein Hormone Subunits: A Comprehensive Review

Abstract: The glycoprotein hormones (GPH) are heterodimers composed of a common α subunit and a specific β subunit. They act by activating specific leucine-rich repeat G protein-coupled receptors. However, individual subunits have been shown to elicit responses in cells devoid of the receptor for the dimeric hormones. The α subunit is involved in prolactin production from different tissues. The human chorionic gonadotropin β subunit (βhCG) plays determinant roles in placentation and in cancer development and metastasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 256 publications
(324 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, free dimeric CGA has been reported to increase lactotrope differentiation and prolactin release (reviewed in ref. 75 ). It has also been reported that pancreatic islets and insulin processing are directly regulated by melanocortins via MC4R ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, free dimeric CGA has been reported to increase lactotrope differentiation and prolactin release (reviewed in ref. 75 ). It has also been reported that pancreatic islets and insulin processing are directly regulated by melanocortins via MC4R ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the pars tuberalis has been reported to be a source of a prolactin secretagogue called tuberalin (73,74). Furthermore, free dimeric CGA has been reported to increase lactotrope differentiation and prolactin release, reviewed in (75). It has also been reported that pancreatic islets and insulin processing are directly regulated by melanocortins via MC4R (76).…”
Section: A Biological Switch For Different States Of Glucose Homeosta...mentioning
confidence: 99%
“…GSEA indicated that gonadotropins and luteinizing hormone signaling pathways might be affected toward the late stage of the disease (10 months). Among leading-edge genes was Cga , which encodes the alpha subunit of glycoprotein hormones (in humans: chorionic gonadotropin, luteinizing hormone, follicle-stimulating hormone, and thyroid stimulating hormone) ( Bellisario et al, 1973 ; Querat, 2021 ). Furthermore, a significant enrichment of inflammatory pathways was only present in 10 months old BACHD vs. WT, where the inflammatory genes such as H2-Aa and Cd74 had comparable expression levels in 2 months old BACHD to WT littermates.…”
Section: Discussionmentioning
confidence: 99%
“…FSHR-1 ligands, the glycoprotein hormone subunit orthologs gpla-1 and gplb-1, act in a common pathway with fshr-1 to regulate neuromuscular function GPLA-1/GPA2 and GPLB-1/GPB5 encode C. elegans orthologs of the glycoprotein hormone subunits GPA2 and GPB5, which are ancestral to all glycoprotein hormones, including FSH in vertebrates (Oishi et al, 2009;Park et al, 2005;Querat, 2021;Van Sinay et al, 2017). GPLA-1/GPA2 and GPLB-1/GPB5 activate FSHR-1 in vitro and act as cognate FSHR-1 ligands in body size regulation .…”
Section: Fshr-1 Acts Upstream Of Canonical G Protein and Lipid Kinase...mentioning
confidence: 99%